Structure of Activities in the Project Model of Science Teaching - Ristanović, Dušan P. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
This paper, using descriptive analytic method, considers possible structure of pupil`s and teacher's activity in project based model in Science teaching. Leaning on Meyer`s structural model of methodic action, author suggests structuring project activities in four stages: preparation stage, procedural stage, process stage, and reflective stage. Accordingly, function of each stage is explained, with special emphasis on the search — a three stage cycle in which pupils explore materials, ideas, or situationsthus encouraging them to work on projects and formulate driving questions, research problems, which are basis for further activity. In conclusion, it is ascertained that the given structure of activities should help pupils in adopting and understanding research procedures, and teachers in perfecting ability of planning, organizing, and conducting a project.
Keywords: driving question; structure; research; Science teaching; Project model of teaching